Life, death and rubbish disposal in Roman Norton, North Yorkshire : excavations at Brooklyn House 2015-16 - Phillips, Janet, (Archaeopress Roman archaeology ;, 2021)
This volume reports on excavations in advance of the development of a site in Norton-on-Derwent, North Yorkshire close to the line of the main Roman road running from the crossing point of the River Derwent near Malton Roman fort to York. This site provided much additional information on aspects of the poorly understood 'small town' of Delgovicia.